Hacking Profits in Real Estate: The Influence of Capital Structure, Liquidity, and External Factors - Faizul Mubarok; Farhan Putra Pramudya; Muhammad Ziyad Izzuddin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study seeks to empirically examine the influence of capital structure, liquidity, firm value, firm size, and external factors on profitability within companies operating in the property and real estate sector listed on the Indonesia Stock Exchange, utilizing sample data from 2018 to 2022. Through purposive sampling, 10 companies were selected as research subjects, employing panel data regression analysis. The findings indicate that liquidity and company size have a negative and significant impact on profitability. Conversely, inflation exerts a positive and significant influence on profitability. However, neither capital structure nor firm value significantly affect profitability. These results contribute to understanding the factors influencing the profitability of property and real estate sector companies within the Indonesian capital market context.